Sterol regulatory element binding protein-1 (SREBP1) gene expression is similarly increased in polycystic ovary syndrome and endometrial cancer - Shafiee, Mohamad Nasir; Mongan, Nigel P.; Seedhouse, Claire; Chapman, Caroline; Deen, Suha; Abu, Jafaru; Atiomo, William (Wiley, 2017)
Introduction: Women with polycystic ovary syndrome (PCOS) have a 3-fold higher risk of endometrial cancer (EC). Insulin resistance and hyperlipidaemia may be pertinent factors in the pathogenesis of both conditions. The aim of this study was to investigate endometrial Sterol Regulatory Element Binding Protein-1 gene (SREBP1) expression in PCOS and EC endometrium, and to correlate endometrial SREBP1 expression with serum lipid profiles. Material and methods: A cross-sectional study was performed at Nottingham University Hospital, United Kingdom. A total of 102 women (PCOS, EC and controls; 34 participants in each group) were recruited. Clinical and biochemical assessments were performed before endometrial biopsies were obtained from all participants. Taqman real-time PCR for endometrial SREBP1 and its systemic protein expression were analysed. Results: The BMI of women with PCOS (29.28 (±2.91) kg/m2) and controls (28.58 (±2.62) kg/m2) was not significantly different. Women with EC had a higher mean BMI (32.22 (±5.70) kg/m2). SREBP1 gene expression was significantly increased in PCOS and EC endometrium compared to controls (p<0.0001). SREBP1 gene expression was positively correlated with BMI (r=0.017, p=0.921) and waist-hip ratio (r=0.023, p=0.544) in PCOS, but this was not statistically significant. Similarly, statistically insignificant positive correlations were found between endometrial SREBP1 gene expression and BMI in EC (r=0.643, p=0.06) and waist-hip ratio (r=0.096, p=0.073). SREBP1 expression was significantly positively correlated with triglyceride in both PCOS and EC (p= 0.028 and p=0.027). Quantitative serum SREBP1 correlated with endometrial gene expression (p<0.05). Conclusions: SREBP1 gene expression is significantly increased in the endometrium of PCOS and EC women compared with controls and positively correlates with serum triglyceride in both PCOS and EC.